The ‘Holistic- Systemic’ Academic Management Model of the Faculty of Tarbiyah and Education, Sunan Kalijaga State Islamic University, Yogyakarta in Disruption Era (Benchmark to Melbourne Graduate School of Education) - Sutrisno, Sutrisno; Radjasa, Radjasa; Istiningsih, Istiningsih; Sa’adah, Miftahus (International Journal of Engineering and Technology, 2018)
The faculty of Tarbiyah and Education at the State Islamic University Sunan Kalijaga Yogyakarta has experienced disorientation in terms of its graduates. Moreover, academic staff and stakeholders are susceptible to disappoint toward the future of the graduates. It is expected that the graduates will be equipped with various skills of teaching as well as the mastery of educational philosophy. In fact, the faculty of Tarbiyah and Education seems to be, to some extent, neglectful to this focus. The faculty has also undergone some perplexity in terms of academic as well as organizational management. To address this issue, the Melbourne Graduate School of Education (MGSE) has been taken as the role model for the improvement of the faculty. This article describes the current situation appear in the Faculty of Tarbiyah and Education as well as the existing state at the Melbourne Graduate School of Education. Then, it proposes the future model of the Faculty of Tarbiyah and Education based on the benchmarking activities done at the Melbourne Graduate School of Education. It is assumed that by implementing the MGSEâ€™s best practices which is suited into the facultyâ€™s specific circumstance, the Faculty of Tarbiyah and Education will be enhanced and gains its focus on teaching and education areas which will likewise improve its graduatesâ€™ performance. Furthermore, this article will also be enlightening for researchers and practitioners in the area of higher education particularly in relation to the management of the faculty of education.Â Â